Unbounded Utility Functions in Expected Utility Theory - Fishburn, Peter C. (Quarterly Journal of Economics, 1976)
Journal Article Unbounded Utility Functions in Expected Utility Theory Get access Peter C. Fishburn Peter C. Fishburn Pennsylvania State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 90, Issue 1, February 1976, Pages 163–168, https://doi.org/10.2307/1886093 Published: 01 February 1976